Experiments on two-phase flow in hydraulic jump on pebbled rough bed: Part 2–Bubble clustering - Farhad Bahmanpouri; Carlo Gualtieri; Hubert Chanson (Water Science and Engineering, 2023)
A survey on bubble clustering in air–water flow processes may provide signiﬁcant insights into turbulent two-phase ﬂow. These processes have been studied in plunging jets, dropshafts, and hydraulic jumps on a smooth bed. As a first attempt, this study examined the bubble clustering process in hydraulic jumps on a pebbled rough bed using experimental data for 1.70 < Fr1 < 2.84 (with Fr1 denoting the inflow Froude number). The basic properties of particle grouping and clustering, including the number of clusters, the dimensionless number of clusters per second, the percentage of clustered bubbles, and the number of bubbles per cluster, were analyzed based on two criteria. For both criteria, the maximum cluster count rate was greater on the rough bed than on the smooth bed, suggesting greater interactions between turbulence and bubbly flow on the rough bed. The results were consistent with the longitudinal distribution of the interfacial velocity using one of the criteria. In addition, the clustering process was analyzed using a different approach: the interparticle arrival time of bubbles. The comparison showed that the bubbly flow structure had a greater density of bubbles per unit ﬂux on the rough bed than on the smooth bed. Bed roughness was the dominant parameter close to the jump toe. Further downstream, Fr1 predominated. Thus, the rate of bubble density decreased more rapidly for the hydraulic jump with the lowest Fr1.